Counterclockwise modular laparoscopic anatomical mesohepatectomy using combined glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches - Zhao, Zonglei; Lyu, Xiaotong; Lyu, Xiaoqin; Kong, Lingqun; Zhao, Baolei; Zhu, Wentao; Wei, Qiang; Lin, Xutao; Cao, Xuefeng; Zhang, Xingyuan (Frontiers in Oncology, 2022)
Background: Although laparoscopic anatomical hepatectomy (LAH) is widely adopted today, laparoscopic anatomic mesohepatectomy (LAMH) for patients with hepatocellular carcinoma (HCC) remains technically challenging. Methods: In this study, 6 patients suffering from solitary liver tumors located in the middle lobe of the liver underwent counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches. To reduce the possibility of releasing cancer cells from the primary tumor, an in situ resection strategy for tumor removal was implemented. In this process, the Glissonean pedicle approach (Takasaki approach) was first used to transect the liver pedicles of segment right anterior (P58) and segment 4 (P4). Second, the hepatic vein-guided approach was performed along the umbilical fissure vein (UFV) to sever the liver parenchyma from the caudal to cranial direction, and the middle hepatic vein (MHV) and anterior fissure vein (AFV) were then disconnected at the root. Last, the hepatic vein-guided approach was once more performed along the ventral side of the right hepatic vein (RHV) to transect the liver parenchyma from the cranial to anterior direction, and the middle lobe of the liver, including the tumor, was removed completely. The entire process was applied in a counterclockwise fashion, and the exposure or transection sequence was P58, and P4, followed by UFV, MHV, AFV, and finally, the liver parenchyma along the ventral side of RHV. Results: The counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches was feasible in all 6 cases. The median duration of the operation was 275 ± 35.07 min, and the mean estimated blood loss was 283.33 ml. No serious postoperative complications, such as pleural effusion, postoperative intra-abdominal hemorrhage, bile leakage, or IAI, occurred, and the mean postoperative hospital stay was 6.83 ± 1.47 days. Conclusions: Counterclockwise modular LAMH using combined Glissonean pedicle (Takasaki approach) and hepatic vein-guided approaches is feasible and may be a good alternative for patients with a centrally located solitary HCC. A multicenter, large-scale prospective randomized controlled trial is necessary to verify the procedure in the future.